Application of standard precautions during patient care in a specialization program - Alejandra Fuenzalida; Valetina Díaz Isla; Andrea Dezerega; Montserrat Mercado Vivallos; Mauricio Toro; Alain Manuel Chaple Gil; Eduardo Fernández (Editorial Ciencias Médicas, 2022)
Introduction: With the increase in infectious diseases during health care, the application of biosecurity standards is essential to avoid cross-contamination. Students in Professional Specialization programs must adhere to a set of standards called standard precautions during patient care. Objective: Determine the degree of application of standard precautions by students of a specialization program during patient care. Materials and methods: A descriptive observational study was conducted. The sample size was 15 students from the Professional Specialization Program in Endodontics of the Faculty of Dentistry of the University of Chile, divided into two groups, day (8-17 h) and evening (18-22 h), who signed an informed consent to participate. They were evaluated in 4 dimensions: "hand washing", "protective barriers" (gloves, mask, hat, protective lenses, breastplate), "risks control of sharp accidents and splashes", and "handling of materials and surfaces". A 60% was established to determine minimum compliance with the standard by comparing both groups. Results: In handwashing, both groups did not reach the minimum compliance with the standard, with an average of 12%. For "protective barriers" both groups achieved minimum compliance, with an average of 63%. In "risk control of sharp accidents and splashes" and "surface handling", none of the groups reached the minimum compliance in these dimensions, with a compliance percentage of 50% and 43% respectively. Conclusions: Most students in the Professional Specialization Program in Endodontics do not correctly apply all standard precautions during care. It is necessary to reinforce in the students the contents related to biosecurity and to increase the supervision and demand in its fulfillment by the teachers.